Do Mind Maps Really Catalyze EFL Grammar Learning? Conjunction as a Case - Bataineh, Ruba Fahmi; Al-Majali, Hiba Ahmad (Universitas Negeri Makassar, 2023)
This study examines the potential effect of mind mapping-based instruction on Jordanian EFL tenth-grade students’ use of additive, adversative, causal and temporal conjunctions. A purposeful sample of two tenth-grade sections was drawn from a public school in Mafraq, Jordan. The two sections were randomly assigned into an experimental group of 14 students, taught through mind mapping, and a control group of 13 students, taught per the guidelines of the prescribed Teacher’s Book. Following an eight-week treatment, the data were collected by means of a post-test. The findings revealed that the experimental group scored significantly higher than the control group in the use of the four types of conjunctions and overall. The study concludes with several pedagogical implications and recommendations for further research.